2009
DOI: 10.31186/jagrisep.8.2.1-11
|View full text |Cite
|
Sign up to set email alerts
|

Respons Komunitas Nelayan Terhadap Modernisasi Perikanan: Studi Kasus Nelayan Suku Bajo Di Desa Lagasa Kabupaten Muna Provinsi Sulawesi Tenggara

Abstract: Fishery modernization by the Government of Indonesian is intended to alleviate fishery community poverty including for Bajau Ethnic fishermen.  This research is aimed at studying the relationship between the meaning of sea and work by fishermen and their acceptance to fishery modernization, impact analyzing of fishery modernization to work pattern, social structure, and the propesperity level.  This research is conducted in Lagasa Village, District Of Muna Southeast Sulawesi where Bajau ethnic stay.  Responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…The low level of education and the lack of participation in training are some of the reasons. The results of the study (Hamzah, 2009) found that modernization by increasing and using fishing gear technology has implications for changes in a fishing community. This definition can only be done with the participation of education, both formal and non-formal education.…”
Section: Recommendations Of Local Governmentmentioning
confidence: 92%
“…The low level of education and the lack of participation in training are some of the reasons. The results of the study (Hamzah, 2009) found that modernization by increasing and using fishing gear technology has implications for changes in a fishing community. This definition can only be done with the participation of education, both formal and non-formal education.…”
Section: Recommendations Of Local Governmentmentioning
confidence: 92%
“…Oleh karena itu, suku Bajo dipandang sangat dekat dengan laut. Dengan begitu, hal yang perlu dikaji lebih dalam adalah suku Bajo dan laut saat ini dapat dipandang sebagao budaya, sumber mencari nafkah ataupun sarana pelestarian lingkungan (Hamzah et al, 2019). Dinamika mengenai suku Bajo yang tidak dapat dilepaskan dengan lautan menjadikan sebuah kajian mengenai suku Bajo sangat menarik.…”
Section: Gambar 3 Masyarakat Bajo Hidup DI Laut Dan Masak Di Atas Per...unclassified
“…Upaya meningkatkan kesejahteraan ekonomi komunitas nelayan terus dilakukan melalui berbagai pendekatan. Diawali dengan Revolusi Biru pada tahun 1980-an yang menekankan pada modernisasi perikanan diharapkan mampu mengatasi kesenjangan pada masayarakat nelayan (Hamzah, 2008). Pada tahun 2008, pemerintah mengeluarkan kebijakan melalui Peraturan Menteri Kelautan dan Perikanan Nomor Per.07/MEN/2008 tentang Bantuan Sosial Pemberdayaan Masyarakat Pesisir dan Pembudidaya Ikan.…”
Section: A Pendahuluan 1 Analisis Situasiunclassified